South Africa's Bank licencing prequirements in light of its banking sector liberalisation commitments under the general agreement on trade in services : a legal perspective - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2015)
Dissertation (LLM)--University of Pretoria, 2014.